Digital education in nursing - Milutinović Dragana; Simin Dragana (Sestrinska reč, 2022)
The coronavirus pandemic caused unprecedented changes in all spheres of life. Education has completely shifted from the dominantly traditional to the digital framework. With that, nurse educators in higher education also started applying different models of innovative digital technologies. For example, the recreational escape room (ER) game, which has gained global popularity in the last decade, has inspired nurse educators to apply it in an educational setting. According to the definition, ER is a game in which a team of players discovers clues solves puzzles and performs tasks in one or more rooms to achieve a specific goal in a limited time, usually "room escape". In educational ER, all problems, challenges and activities are called a puzzle, while the term room means the space in which it is realized. Therefore, educational ER can be on-site and online. ER has found its place in the learning environment because it brings time-limited authentic situations from the natural professional environment. To successfully complete the mission and "escape from the room", students, in addition to engagement that encourages critical thinking, intensively communicate and cooperate with each other. This paper presents the application of online educational ER in the subject Fundamentals of Nursing.